The mediating effect of intrusive rumination on the relationship between illness uncertainty and fear of cancer recurrence in breast cancer survivors - Alper Türkel; Nur Nihal Türkel; Ahmet Kadıoğlu; Mutlu Doğan; İrem Ekmekçi Ertek (BMC Women's Health)
Abstract Background Recently, increased awareness of early diagnosis and treatment options has led to an increase in the number of breast cancer survivors. Psychosocial interventions to increase the quality of life in this group are gaining importance. One of the most common psychological problems in breast cancer survivors is fear of cancer recurrence (FCR). It is essential to elucidate the mechanisms of FCR. Aims: This study aimed to examine the mediating effect of intrusive rumination on the relationship between illness uncertainty and FCR in breast cancer survivors. Methods The study was designed to be cross-sectional, and 204 breast cancer survivors were included. Participants were given the Mishel Uncertainty in Illness Scale-Community form (MUIS-C), the severity subscale of the Fear of Cancer Recurrence Inventory, and the Event-Related Rumination Inventory-intrusive rumination subscale. Correlation analyses were conducted, and the structural equation method evaluated the mediation effect. Results Most participants (74%) reported some degree of FCR. A significant positive relationship was found between illness uncertainty and FCR (r = 0.325; p ≤ 0.001). The path analysis showed that intrusive rumination partially mediates this relationship. Conclusions This study’s results shed light on the relationship between illness uncertainty, rumination, and FCR. Planning psychoeducation programs during follow-up to reduce illness uncertainty may positively affect FCR. In addition, metacognitive therapies that can functionalize the ruminative thinking style can also effectively intervene in FCR.